Agricultural trade reform and the Doha development agenda - Anderson, Kym; Martin, Will (Trade and development series, 2006)
"Anderson and Martin examine the extent to which various regions, and the world as a whole, could gain from multilateral trade reform over the next decade. They use the World Bank's linkage model of the global economy to examine the impact first of current trade barriers and agricultural subsidies, and then of possible outcomes from the World Trade Organization's Doha round. The results suggest moving to free global merchandise trade would boost real incomes in Sub-Saharan Africa and Southeast Asia (and in Cairns Group countries) proportionately more than in other developing countries or high-income countries. Real returns to farm land and unskilled labor and real net farm incomes would rise substantially in those developing country regions, thereby alleviating poverty. A Doha partial liberalization could take the world some way toward those desirable outcomes, but more so the more agricultural subsidies are disciplined and applied tariffs are cut."